Impact of the histological regression grade of the primary tumor and regional lymph nodes after neoadjuvant chemoradiotherapy on survival of patients with gastric cancer: two case reports - V. Yu. Skoropad; D. D. Kudriavtsev; L. N. Titova; T. A. Agababjan; E. S. Zhavoronkovа; S. V. Gamayunov; D. A. Vinokurova (Сибирский онкологический журнал, 2020)
Background. Stomach cancer remains one of the most common malignancies worldwide, with high incidence rates and low rates of long-term treatment outcomes. Neoadjuvant therapy currently is increasingly being considered the standard therapy for locally advanced gastric and cardioesophageal cancers. A complete pathological response of the tumor has been reported to be observed in 8-20 % of patients. However, there is no guarantee that the evidence of pathological complete response will improve the cure results in all patients, and very little is known about prognostic factors after neoadjuvant therapy.Case descriptions. Two clinical cases of locally advanced gastric cancer were described. The patients were treated with neoadjuvant chemoradiotherapy followed by D2 gastrectomy. Accelerated hyperfractionated radiotherapy (1 + 1.5 Gy/ day) to a total dose of 45 Gy at intervals of 4-5 hours was administered concurrently with chemotherapy (capecitabine: 1850 mg/m2 orally twice daily at 12-hour interval; oxaliplatin: 85 mg/m2 intravenously on days 1 and 21). Histological examination revealed complete histological regression of the primary tumor in two cases. However, in one of the cases, metastases in regional lymph nodes with grade 2 histological tumor regression were revealed. In the first case, the patient is still alive with no evidence of disease recurrence at over 6-years after treatment. In the second case, the patient died of the disease progression 3 years after treatment.Conclusion. The data obtained are consistent with the few published studies reporting that pathological complete response to neoadjuvant therapy of not only the primary tumor but also regional lymph nodes is the key point determining the effectiveness of the combined modality treatment.